Experimental and numerical performance analyses of Dish-Stirling cavity receivers: Radiative property study and design. (15th February 2019) - Garrido, Jorge; Aichmayer, Lukas; Abou-Taouk, Abdallah; Laumert, Björn
Abstract: The solar receiver performance has a direct impact on the CSP power plant performance and, thereby, its levelized cost of electricity. Improved receiver designs supported by new advanced numerical tools and experimental validation campaigns directly help to make CSP technology more competitive. This paper presents an experimental and numerical investigation of the influence of the cavity receiver radiative properties and the thermal power input on the Dish-Stirling performance. Three cavity coatings are experimentally investigated: the original cavity material ( Fiberfrax 140 ), Pyromark 2500 and Pyro-paint 634-ZO . Moreover, simulations validated with the experimental measurements are utilized to define a higher performance cavity receiver for the Eurodish system. The results indicate that the absorptivity of the cavity should be as low as possible to increase the receiver efficiency whereas the optimum emissivity depends on the operating temperatures. If the cavity temperature is lower than the absorber temperature, low emissivities are recommended and vice-versa. All material/coatings analyzed for the cavity provide similar receiver efficiencies, being Fiberfrax 140 slightly more efficient. Finally, a total receiver efficiency of 91.5% is reached by the proposed Eurodish cavity receiver when operating under the most favorable external conditions. Highlights: Performed a parametric experimental study of cavity coatings and thermal powers. Large set of experimental data collected capturing detailed performance parameters. System simulations validated against multiple parameters and operating conditions. Sensitivity studies of the influence of coatings on the cavity receiver efficiency. Higher efficiency cavity receiver designed maximizing the total electric production.